Halogenated phenazinothiadiazoles: electron-transporting materials - Zong, Wansheng; Hippchen, Nikolai; Dittmar, Benedikt; Elter, Maximilian; Ludwig, Philipp; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Asian journal of organic chemistry, 2023)
Triisopropylsilyl-(TIPS)-alkynylated phenazinothiadiazoles were prepared by the condensation of halogenated ortho-quinones and TIPS-alkynylated 5,6-diamino-2,1,3-benzothiadiazole with different combinations of halogen substituents. The compounds pack in brickwall motif of head-to-head dimers featuring intermolecular S−N contacts and short π-π distances, suggesting their suitability as n-channel materials in organic thin film transistors. The halogenated phenazinothiadiazoles show electron mobilities μmax ranging between 0.14 cm2 V−1 s−1 and 0.76 cm2 V−1 s−1.
Version des Artikels: November 20, 2023
Gesehen am 10.01.2024